Ceramide in cerebrovascular diseases - Yuan, Huiqi; Zhu, Bin; Li, Cao; Zhao, Zhigang (Frontiers in Cellular Neuroscience, 2023)
Ceramide, a bioactive sphingolipid, serves as an important second messenger in cell signal transduction. Under stressful conditions, it can be generated from de novo synthesis, sphingomyelin hydrolysis, and/or the salvage pathway. The brain is rich in lipids, and abnormal lipid levels are associated with a variety of brain disorders. Cerebrovascular diseases, which are mainly caused by abnormal cerebral blood flow and secondary neurological injury, are the leading causes of death and disability worldwide. There is a growing body of evidence for a close connection between elevated ceramide levels and cerebrovascular diseases, especially stroke and cerebral small vessel disease (CSVD). The increased ceramide has broad effects on different types of brain cells, including endothelial cells, microglia, and neurons. Therefore, strategies that reduce ceramide synthesis, such as modifying sphingomyelinase activity or the rate-limiting enzyme of the de novo synthesis pathway, serine palmitoyltransferase, may represent novel and promising therapeutic approaches to prevent or treat cerebrovascular injury-related diseases.